=========================================================
How to get this answer:
Locate 6 on the x axis. Draw an arrow down until you reach the f(x) curve, then move to the left until you reach the y axis. We started at x = 6 and ended on y = -6. See the diagram below for this process in action.
So basically f(6) = -6. Visually the point (6,-6) is on the f(x) curve.
Through similar steps, we see that g(5) = -5
Therefore,
4*f(6) - 6*g(5) = 4*(-6) - 6*(-5) = -24 + 30 = 6
โ7(9x โ 5)
Answer:
-63x+35
Step-by-step explanation:
-7 x 9x is -63x
-7- -5=35
-63x+35
4
6.9
8.3
no mode
Answer:
The given statement:
You cannot bisect an angle using paper folding constructions is a False Statement.
Step-by-step explanation:
The construction of a angle bisector with the help of paper folding is done by:
Answer:
The vertex is a maximum.
Step-by-step explanation: